Can Transabdominal Cervical Length Measurement Exclude Short Cervix? - Rhoades, Janine S.; Park, Jennifer M.; Stout, Molly J.; Macones, George A.; Cahill, Alison G.; Tuuli, Methodius G. (American Journal of Perinatology, 2016)
Objective This study aims to determine if transabdominal (TA) cervical length may be used to rule out a short cervix on transvaginal (TV) ultrasound.Study Design We conducted a prospective cohort study of women undergoing routine anatomic survey at 17 to 23 weeks gestation. TA and TV cervical length measurements were obtained in each patient. A short cervix was defined as TV cervical length < 30 mm. Predictive characteristics were calculated for different cutoff values of TA cervical length.Results There were 404 patients enrolled, a TA cervical length could not be obtained in 83 women (20.6%) and 318 women had both TA and TV measurements. Of those, 14 (4.4%) had a TV cervical length < 30 mm. TA cervical length measurement ≥ 35 mm excluded the possibility of TV cervical length < 30 mm (negative predictive value, 99.5%; 95% confidence interval [CI], 97.4; 100%). In our cohort, 67.6% (95% CI, 62.2; 72.7%) of TV ultrasounds could have been avoided using a TA cervical length cutoff of ≥ 35 mm.Conclusion ATA cervical length of at least 35 mm excludes a short cervix of < 30 mm. While TA cervical length screening may not be feasible in 1 in 5 women, it may be used to decrease the burden of universal TV cervical length screening.
Keywords: cervical length; short cervix; transabdominal ultrasound; transvaginal ultrasound